2000
DOI: 10.1046/j.1526-100x.2000.80025.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Northwest Florida Sandhills Through Harvest of Invasive Pinus clausa

Abstract: Across much of the southeastern U.S.A., sandhills have become dominated by hardwoods or invasive pine species following logging of Pinus palustris (longleaf pine) and fire suppression. At Eglin Air Force Base where this study was conducted, Pinus clausa (sand pine) has densely colonized most southeastern sandhill sites, suppressing groundcover vegetation. The objectives of this study were: to determine if suppressed groundcover vegetation recovers following the removal of P. clausa; to compare species composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…This approach might be successful in situations where encroachment has resulted in major structural alterations, such as canopy closure or development of midstory vegetation, which might inhibit the reestablishment of historic fire regimes (Sarr et al, 2004). Although active removal of encroaching woody vegetation has produced preliminary success in some conifer and aspen systems (Moore et al, 1999;Provencher et al, 2000;Jones et al, 2005), it is not known whether removing encroaching vegetation will restore historic regeneration dynamics (Allen et al, 2002). More research is needed, especially in understudied ecosystems such as oak savannas.…”
Section: Introductionmentioning
confidence: 99%
“…This approach might be successful in situations where encroachment has resulted in major structural alterations, such as canopy closure or development of midstory vegetation, which might inhibit the reestablishment of historic fire regimes (Sarr et al, 2004). Although active removal of encroaching woody vegetation has produced preliminary success in some conifer and aspen systems (Moore et al, 1999;Provencher et al, 2000;Jones et al, 2005), it is not known whether removing encroaching vegetation will restore historic regeneration dynamics (Allen et al, 2002). More research is needed, especially in understudied ecosystems such as oak savannas.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we believe that reductions in stems per quadrat in By comparison, the decreases in species richness over the course of this study suggest relatively little recruitment of new species occurred regardless of treatment. Provencher et al (2000) found that species richness also decreased after the application of felling and slash burning in Florida's sandhill vegetation. However, Provencher et al (2000) observed an increase in species richness two years after treatment application.…”
Section: Discussionmentioning
confidence: 97%
“…Provencher et al (2000) found that species richness also decreased after the application of felling and slash burning in Florida's sandhill vegetation. However, Provencher et al (2000) observed an increase in species richness two years after treatment application. Results from pRDA (see Figure 8) suggest a transition from pretreatment species composition dominated by mesic or forest species to post-treatment tallgrass prairie species.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations